‘Working relationships’ across difference - a realist review of community engagement with malaria research - Vincent, R; Adhikari, B; Duddy, C; Richardson, E; Wong, G; Lavery, J; Molyneux, S (F1000Research, 2022)
Background: Community engagement (CE) is increasingly accepted as a critical aspect of health research, because of its potential to make research more ethical, relevant and well implemented. While CE activities linked to health research have proliferated in Low and Middle Income Countries (LMICs), and are increasingly described in published literature, there is a lack of conceptual clarity around how engagement is understood to ‘work’, and the aims and purposes of engagement are varied and often not made explicit. Ultimately, the evidence base for engagement remains underdeveloped. Methods: To develop explanations for how and why CE with health research contributes to the pattern of outcomes observed in published literature, we conducted a realist review of CE with malaria research – a theory driven approach to evidence synthesis. Results: We found that community engagement relies on the development of provisional ‘working relationships’ across differences, primarily of wealth, power and culture. These relationships are rooted in interactions that are experienced as relatively responsive and respectful, and that bring tangible research related benefits. Contextual factors affecting development of working relationships include the facilitating influence of research organisation commitment to and resources for engagement, and constraining factors linked to the prevailing ‘dominant health research paradigm context’, such as: differences of wealth and power between research centres and local populations and health systems; histories of colonialism and vertical health interventions; and external funding and control of health research. Conclusions: The development of working relationships contributes to greater acceptance and participation in research by local stakeholders, who are particularly interested in research related access to health care and other benefits. At the same time, such relationships may involve an accommodation of some ethically problematic characteristics of the dominant health research paradigm, and thereby reproduce this paradigm rather than challenge it with a different logic of collaborative partnership.